The Future of Information Science E ducatio n in Canada: Issues and D iscussion - Cross, Emma (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
This poster visually presents issues in the future of information science education in Canada. The poster incorporates research completed for development of the new Bachelor of Information Technology – Information Resource Management program at Carleton University, launched in Fall 2016. http://bitdegree.ca/ In conclusio n, key strategies for the future will be identified.